Rancang Bangun Sistem Informasi Reservasi Ruangan Berbasis Web pada Gereja Kristus Cibinong - Stenly George Mooy; Muhammad Ardiansyah; Muhammad Rizqi; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2026)
This study aims to design and develop a web-based room reservation information system at Gereja Kristus Cibinong. The existing manual reservation process often causes scheduling conflicts, recording errors, and delays in information delivery. The Prototype development method was applied to accommodate user requirements iteratively. The system was designed using UML modeling and a relational database. The implementation results indicate that the system provides real-time room availability information, simplifies reservation processes, and assists administrators in managing reservation data. System testing demonstrated that all features functioned properly according to user requirements.